Adolescent developmental assets and longitudinal weight status and psychosocial health outcomes: Exploratory analysis from a youth cohort study in Taiwan - Meng-Che Tsai; Jennifer M.T. Ng; Yi-Fang Yu; Carol Strong; Yi-Ping Hsieh; Yi-Ching Lin; Chung-Ying Lin (Pediatrics and Neonatology)
Backgrounds: Asset-based youth development has been proposed to be associated with health behaviors and psychological well-being in adolescents. This study aims to extend the current knowledge regarding the effects of positive youth development on weight status and psychosocial health outcomes in young adulthood using a large representative longitudinal sample. Methods: Data were retrieved from the Taiwan Youth Project that comprised a longitudinal cohort of adolescents (N = 2688) surveyed at grades 7, 8, 9, and 12, and at age 22. Principal component analysis was used to construct developmental asset scores based on 35 items selected from the relevant questions at wave 1. Outcomes were standardized scores of body mass index, self-rated healthiness and happiness, depressive symptomology and deviant behaviors in the subsequent waves. Generalized estimating equation analysis was applied to assess the impact of developmental assets on these repeatedly measured outcome variables. Results: As compared to those with the highest quintile level of developmental assets, individuals with the lowest quintile level were more likely to rate themselves unhealthy (β = 0.33 [95% confidence interval 0.26, 0.40]) and unhappy (β = 0.47 [0.41, 0.54]) and report more depressive symptomatology (β = 4.18 [3.35, 5.01]) and deviant behaviors (β = 0.63 [0.44, 0.81]). No association was found between body mass index and developmental asset scores. Conclusion: The results concluded a longitudinal association between adolescent developmental assets and psychological and behavioral health outcomes. Further research may be required to investigate whether positive youth development could be translated into long-term benefits in adult physical conditions, such as obesity.